Intellectual and Developmental Disabilities, Spirituality and Religion: A Systematic Review 1990-2015 - Sango, Precious Nonye (Journal of disability & religion, 2017)
Over the past two decades, research on religion and spirituality has begun to gain momentum. Nevertheless, to the authors' knowledge, a systematic review of empirical research in the field of intellectual and developmental disabilities (IDD), social care services, and spirituality has not been carried out in the last 20 years. Six psychology-, IDD-, religion-, and health-related journals were searched in addition to two databases. Empirical articles published between 1990 and 2015 on religion, religiosity, spirituality, spiritual or religious care and people with IDD and related terms were identified and examined. Of the 57 publications identified, only 8.9% met the inclusion criteria and were reviewed. The five empirical articles included in this review were thematically analyzed, yielding four main themes in relation to spiritual or religious care: understanding of spiritual or religious concepts, support to participate in spiritual or religious activities, spiritual or religious practices in relation to self-identity, and barriers to spiritual or religious care provision. The authors conclude that more empirical and original research in relation to the spiritual care of people with IDD residing in IDD care services is needed.